LAMINAR FLOW OVER SLOPED DOWNSTREAM HEATED BOTTOM WALL BEHIND A BACKWARD-FACING STEP - Bayraktar, Seyfettin (YILDIZ TECHNICAL UNIV, 2020)
In the present three-dimensional study, laminar flow over a backward-facing step was investigated in the framework of the finite volume method for various Reynolds numbers ranging from 100 to 1000. Attempts were made to clarify the effects of the slope of the downstream heated bottom wall behind the step on the reattachment length and heat transfer. It was found that the length of the recirculation region changes slightly with the slope angles at lower Reynolds numbers while it changes dramatically as Reynolds number increases. The longest length of the recirculation region was obtained at the highest slope angle in the negative vertical-direction while the shortest one was determined at the maximum slope angle in the positive vertical direction. Increasing slope angles in both directions also provide a higher local Nusselt number in some distance behind the step.
Keywords: Backward-facing step; laminar flow; computational fluid dynamics; flow separation; reattachment length; heat transfer; CONVECTION; Engineering